The Hierarchy-of-Hypotheses Approach from a Philosophy of Science Perspective. (2nd December 2020) - Schurz, Gerhard
Abstract: I investigate Heger and Jeschke's account of hierarchies of hypotheses (HoHs) from a philosophy of science perspective. HoHs can be theory driven or evidence driven. Theory-driven HoHs fit well with standard representations of hierarchical theory nets (HTNs) in the philosophy of science. A disadvantage of the development of theory-driven HoHs is that they neglect hypotheses describing the effects of combinations of causes; this disadvantage can be removed by adding an additional layer of system conditions. Evidence-driven HoHs additionally include kinds of empirical tests by means of which certain hypotheses in the HoH are tested. This aspect of HoHs goes beyond standard HTNs in the philosophy of science and is highly fruitful; however, it leads to certain problems concerning the relation between causal hypotheses and empirically testable correlation claims.